PENGARUH RETURN ON EQUITY, RETURN ON ASSETS, EARNING PER SHARE, DAN DIVIDEN PER SHARE TERHADAP MARKET VALUE ADDED - Nadiatun Masleha; Dirvi Surya Abbas; Imam Hidayat; Imas Kismanah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
The purpose of this study was to determine the effect ofreturn on equity, return on assets, earnings per share and dividen per share on market value added tn various industrial sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2021 period. The population of this study includes all various industrial sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2021 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria. 9 companies were selected to be the research samples. The type of data used ts secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that the variables return on equity and return on assets had no effect on market value added, the variable earnings per share has a effect on market value added, and the variable dividen per share has a effect on market value added.